Generation Y and the Shift to Electric Vehicles in Indonesia: Exploring Key Drivers and Barriers - Rachmawati, Indira; Al Amin, Ichwan Faiz (Penerbit Goodwood, 2025)
Purpose: Compared With other Asian countries, the usage rate of electric vehicles in Indonesia remains slow owing to a lack of public interest. This paper explores some significant factors that affect the interest of electric vehicles for Gen Y EV products, including environmental concerns and individual consequences. Research Methodology: We extend the previous study by adding other variables, including individual and environmental consequences. Data from 446 respondents were collected through a judgmental sampling procedure and analyzed using partial least squares structural equation Modeling. Results: The results showed that attitudes towards the five dimensions of the UTAUT-2 model significantly influenced intention to purchase. However, attitude did not mediate the relationship between habit and purchase intention. On the other hand, attitude mediation vastly influences not only the association between individual consequences and purchase intention, but also that between environmental concerns and purchase intention. On the other hand, subjective norms also have a positive influence on purchase intention, while perceived risk is not considered to affect the purchasing decisions of Generation Y. Conclusions: This study found that Generation Y’s purchase intention toward electric vehicles in Indonesia is significantly influenced by favorable attitudes formed through factors such as performance expectancy, ease of use, price value, personal benefits, and environmental concern. Social influence and perceived behavioral control also play important roles, while perceived risk was found to be insignificant in affecting purchasing decisions. Limitations: This research is limited to the perspective of Generation Y in Indonesia and may not reflect the behavioral intentions of other generational cohorts or regions. Contributions: These conclusions contribute to the growing body of knowledge on sustainable mobility by integrating UTAUT-2 and TPB frameworks to identify critical behavioral determinants among Generation Y. The insights provide valuable implications for electric vehicle manufacturers, marketers, and policymakers to craft more targeted, effective strategies aimed at increasing EV adoption.